Solve using the quadratic formula
This lesson shows how to solve using the quadratic formula. To use the quadratic formula, you need to identify a, b, and c in the standard of a quadratic equation
Quadratic Formula is x = (b ± √(b
^{2}  4ac))/2a
The standard form is ax
^{2} + bx + c = 0
1) for 6x
^{2} + 8x + 7 = 0 we get a = 6, b = 8, and c = 7
2) for x
^{2} + 8x  7 = 0 we get a = 1, b = 8, and c = 7
2) for x
^{2}  8x + 7 = 0 we get a = 1, b = 8, and c = 7
Example #1:
Solve using the quadratic formula x
^{2} + 8x + 7 = 0
a = 1, b = 8, and c = 7
x = (b ± √(b
^{2}  4ac)) / 2a
x = (8 ± √(8
^{2}  4 × 1 × 7)) / 2 × 1
x = (8 ± √(64  4 × 1 × 7)) / 2
x = (8 ± √(64  4 × 7)) / 2
x = (8 ± √(64  28)) / 2
x = (8 ± √(36)) / 2
x = (8 ± 6 ) / 2
x
_{1} = (8 + 6 ) / 2
x
_{1} = (2 ) / 2
x
_{1} = 1
x
_{2} = (8  6 ) / 2
x
_{2} = (14 ) / 2
x
_{2} = 7
Example #2:
Solve using the quadratic formula 4x
^{2}  11x  3 = 0
a = 4, b = 11, and c = 3
x = (b ± √(b
^{2}  4ac)) / 2a
x = ( 11 ± √( (11)
^{2}  4 × 4 × 3)) / 2 × 4
x = (11 ± √(121  4 × 4 × 3)) / 8
x = (11 ± √(121  4 × 12)) / 8
x = (11 ± √(121 + 48)) / 8
x = (11 ± √(169)) / 8
x = (11 ± 13 ) / 8
x
_{1} = (11 + 13 ) / 8
x
_{1} = (24 ) / 8
x
_{1} = 3
x
_{2} = (11  13 ) / 8
x
_{2} = (2 ) / 8
x
_{2} = 1/4
Example #3:
Solve using the quadratic formula x
^{2} + x  2 = 0
a = 1, b = 1, and c = 2
x = (b ± √(b
^{2}  4ac)) / 2a
x = ( 1 ± √( (1)
^{2}  4 × 1 × 2)) / 2 × 1
x = (1 ± √(1  4 × 1 × 2)) / 2
x = (1 ± √(1  4 × 2)) / 2
x = (1 ± √(1 + 8)) / 2
x = (1 ± √(9)) / 2
x = (1 ± 3 ) / 2
x
_{1} = (1 + 3 ) / 2
x
_{1} = (2) / 2
x
_{1} = 1
x
_{2} = (1  3 ) / 2
x
_{2} = (4 ) / 2
x
_{2} = 2

Oct 02, 19 04:34 PM
Why multiply before adding? The common sense behind doing multiplication before addition
Read More
New math lessons
Your email is safe with us. We will only use it to inform you about new math lessons.